Student’s Comparative Analysis Towards the Teaching-Learning System through E-Learning - Ersan Suria Pranoto; Haryadi Sarjono (Bina Nusantara University, 2011)
The purpose of this study was to measure the student response in comparison between Management Department and Accounting Department at the Faculty of Economics, University of Bunda Mulia, against a system of learning in the e-learning system based. The samples are taken by using non-probability sampling method that is very much purposive. The amount of data to be collected as many as 300 students (respondents) conducted in a proportion as of for the Accounting Department samples of 150 respondents were taken and from the Department of Management also 150 respondents were taken, with a standard error in around 1%. The amount of data is adjusted to the time of data collection conducted during the months of March to May 2008, this was also during the lectures take place in the second semester of 2007/2008. For the idea of applying the e-learning system based, the result in the major of accounting, which are 76%, said that the idea seems to be right if e-Learning is applied but for the Department of Management students, only 32% of students who was responded quite well.